2015
DOI: 10.1186/s12885-015-1444-1
|View full text |Cite
|
Sign up to set email alerts
|

Polish experience of lenalidomide in the treatment of lower risk myelodysplastic syndrome with isolated del(5q)

Abstract: BackgroundLenalidomide has been approved for the treatment of lower-risk myelodysplastic syndrome (MDS) with 5q deletion (del(5q)). We present for the first time a retrospective analysis of low-risk MDS with isolated del5q treated with lenalidomide, outside the clinical trials.Methods36 red blood cell (RBC) transfusion-dependent patients have been included in the study. Patients received lenalidomide 10 mg/day on days 1–21 of 28-day cycles.Results91.7 % of patients responded to lenalidomide treatment: 72.2 % a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The overall rates of HI-E were presented in twelve articles [15,18,2026,28–30]. High heterogeneity of the overall rate of HI-E was found from the data ( P < 0.001, I 2 = 97.0%), and thus the random-effect model was chosen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall rates of HI-E were presented in twelve articles [15,18,2026,28–30]. High heterogeneity of the overall rate of HI-E was found from the data ( P < 0.001, I 2 = 97.0%), and thus the random-effect model was chosen.…”
Section: Resultsmentioning
confidence: 99%
“…AEs of lenalidomide and relevant data were presented in ten articles [14,15,18,20,21,2326,30]. All studies investigated the incidences of grades 3–4 AEs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[16][17][18][19][20][21] The discovery of lenalidomide as an effective treatment in patients with a del(5q) abnormality has further cemented the role of genetic studies in the diagnosis and treatment of the patient with MDS. [22][23][24][25] Recent studies in MDS have shown frequent somatic mutations in the spliceosomal machinery (eg, SFB31, SRSF2, U2AF1, ZRSR2), epigenetic modifiers (eg, TET2, DNMT3A, IDH2/1, EZH2, ASXL1), signaling transducer, transcription factors, and other important gene targets (eg, RUNX1, TP53, NRAS, STAG2, CBL, ETV6). [3][4][5][6][7][8] This molecular information has exhibited value in refining the MDS prognostic risk stratification scheme and may improve therapy response prediction and choice of potential targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, selection of particular treatment may rely on the presence of specific chromosomal aberrations. Low-risk, transfusion-dependent MDS patients with del(5q) are reported to respond well to lenalidomide [ 28 30 ]. So accurate detection of del(5q) is not only important for precise diagnosis of MDS, but also vital for individualized treatment of MDS patients.…”
Section: Common Chromosomal Aberrations In Mdsmentioning
confidence: 99%